Decoding signs in general geographic mapping (Journal of Geography and Environmental Management, 2019)
The given article considers the issues of terrain objects’ discernment by their qualitative and quarantitative characteristicswith conferment of appropriate symbols in accordance with the government instructions concerning the deciphering oflarge scale aerial photographs and photo plans for the purpose of the land organization necessary for the compilation ofthe large scale geographic (topographic) maps used in general and applied sciences.